Advancing quality and safety of perinatal services in India: opportunities for effective midwifery integration. Issue 8 (16th April 2022) - Vedam, Saraswathi; Titoria, Reena; Niles, Paulomi; Stoll, Kathrin; Kumar, Vishwajeet; Baswal, Dinesh; Mayra, Kaveri; Kaur, Inderjeet; Hardtman, Pandora
Abstract: India has made significant progress in improving maternal and child health. However, there are persistent disparities in maternal and child morbidity and mortality in many communities. Mistreatment of women in childbirth and gender-based violence are common and reduce women's sense of safety. Recently, the Government of India committed to establishing a specialized midwifery cadre: Nurse Practitioners in Midwifery (NPMs). Integration of NPMs into the current health system has the potential to increase respectful maternity care, reduce unnecessary interventions, and improve resource allocation, ultimately improving maternal–newborn outcomes. To synthesize the evidence on effective midwifery integration, we conducted a desk review of peer-reviewed articles, reports and regulatory documents describing models of practice, organization of health services and lessons learned from other countries. We also interviewed key informants in India who described the current state of the healthcare system, opportunities, and anticipated challenges to establishing a new cadre of midwives. Using an intersectional feminist theoretical framework, we triangulated the findings from the desk review with interview data to identify levers for change and recommendations. Findings from the desk review highlight that benefits of midwifery on outcomes and experience link to models of midwifery care, and limited scope of practice and prohibitive practice settings are threats to successful integration. Interviews with key informants affirm the importance of meeting global standards for practice, education, inter-professional collaboration and midwifery leadership. Key informants noted that the expansion of respectful maternity care and improved outcomes will depend on the scope and model of practice for the cadre. Domains needing attention include building professional identity; creating a robust, sustainable education system; addressing existing inter-professional issues and strengthening referral and quality monitoring systems. Public and professional education on midwifery roles and scope of practice, improved regulatory conditions and enabling practice environments will be key to successful integration of midwives in India.